Requirements Engineering: Foundation for Software Quality: 20th International Working Conference, REFSQ 2014, Essen, Germany, April 7-10, 2014. Proceedings - Salinesi, Camille (Lecture notes in computer science, 2014)
This book constitutes the refereed proceedings of the 20th International Working Conference on Requirements Engineering: Foundation for Software Quality, REFSQ 2014, held in Essen, Germany, in April 2013. The 23 papers presented were carefully reviewed and selected from 89 submissions. The REFSQ conference is organised as a three-day symposium with two days devoted to scientific papers presentation with a one-day industry track in-between. Both the industry and scientific presentations concern a variety of topics, which shows the liveliness of the requirements engineering domain. These topics are for instance: scalability in RE, communication issues, compliance with law and regulations, RE for self adaptive systems, requirements traceability, new sources of requirements, domain specific RE, Natural Language issues, and of course games. 'Games for RE and RE for Games' was the special topic of REFSQ 2014. This is materialized by a plenary session at the conference, and by a keynote given by Catherine Rolland, a serious games expert and project manager at KTM Advance, a French company specialized in serious games
Literaturangaben
Keywords: Konferenzschrift; Qualitätssicherung; Softwareprodukt; Requirements engineering